Mapping information security standard ISO 27002 to an ontological structure. (14th November 2016) - Fenz, Stefan; Plieschnegger, Stefanie; Hobel, Heidi
Abstract : Purpose: The purpose of this paper is to increase the degree of automation within information security compliance projects by introducing a formal representation of the ISO 27002 standard. As information is becoming more valuable and the current businesses face frequent attacks on their infrastructure, enterprises need support at protecting their information-based assets. Design/methodology/approach: Information security standards and guidelines provide baseline knowledge for protecting corporate assets. However, the efforts to check whether the implemented measures of an organization adhere to the proposed standards and guidelines are still significantly high. Findings: This paper shows how the process of compliance checking can be supported by using machine-readable ISO 27002 control descriptions in combination with a formal representation of the organization's assets. Originality/value: The authors created a formal representation of the ISO 27002 standard and showed how a security ontology can be used to increase the efficiency of the compliance checking process.